PENGARUH JUMLAH KOMITE AUDIT, UKURAN PERUSAHAAN DAN OPINI AUDIT TERHADAP AUDIT DELAY : Studi Empiris Pada Perusahaan yang Terdaftar dalam Indeks LQ45 di Bursa Efek Indonesia tahun 2018-2022 - Satiman, Satiman; Tamaya, Eka Windha (JURNAL AKUNTANSI BARELANG, 2024)
The study aims to analyze the impact of the number of audit committees, company size, and audit opinions on Audit Delay. The research was carried out by analyzing the financial statements of companies listed in the LQ45 index on the Indonesian Stock Exchange (IDX) during the period from 2018 to 2022. The sample used in this study was 23 companies that were listed consistently in the Index of LQ45, on the Indonesia Stock Exchange, for the period 2018 to 2022 using purposive sampling techniques. The data used for the sample research is secondary data from financial statements and annual reports that can be accessed through the IDX website and several corporate websites. The variables used in this study are Number of Audit Committees (X1) as the first free variable, the Company Size (X2) as the second free variabel, and Audit Opinion as the third free variables and the Audit Delay (Y) as the bound variable. The methodology used in this study is a panel data regression method. Analysis of research results using EViews 12 software. Research shows that the best model is Random Effect Model (REM). The results of this study showed that the number of audit committees partially had no influence on the audi delayt, the size of the company partially influenced the delays in the audits, the opinion of the audit partially did not influence the Audit Delay, and simultaneously the number of audit committees, the company size, and the audit opinion had an influence upon the Audit Delay. Keywords: Number of Audit Committees; Company Size; Audit Opinion; Audit Delay